2014
DOI: 10.1371/journal.pone.0100038
|View full text |Cite
|
Sign up to set email alerts
|

Local Barriers and Solutions to Improve Care-Seeking for Childhood Pneumonia, Diarrhoea and Malaria in Kenya, Nigeria and Niger: A Qualitative Study

Abstract: We present qualitative research findings on care-seeking and treatment uptake for pneumonia, diarrhoea and malaria among children under 5 in Kenya, Nigeria and Niger. The study aimed to determine the barriers caregivers face in accessing treatment for these conditions; to identify local solutions that facilitate more timely access to treatment; and to present these findings as a platform from which to develop context-specific strategies to improve care-seeking for childhood illness. Kenya, Nigeria and Niger ar… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

10
88
3

Year Published

2016
2016
2023
2023

Publication Types

Select...
9
1

Relationship

0
10

Authors

Journals

citations
Cited by 82 publications
(101 citation statements)
references
References 25 publications
(36 reference statements)
10
88
3
Order By: Relevance
“…This was supported by KIIs reports that large workloads and few health personnel were among the main causes of delayed services. Similar findings were reported in a study carried out at Homa bay County, Kenya, where long queues or delays at the health facility were found to contribute to delays in seeking care at the hospitals [28]. Other studies done in South Africa, Australia and Central America also reported similar findings, [29,30,31,32].…”
Section: Discussionsupporting
confidence: 86%
“…This was supported by KIIs reports that large workloads and few health personnel were among the main causes of delayed services. Similar findings were reported in a study carried out at Homa bay County, Kenya, where long queues or delays at the health facility were found to contribute to delays in seeking care at the hospitals [28]. Other studies done in South Africa, Australia and Central America also reported similar findings, [29,30,31,32].…”
Section: Discussionsupporting
confidence: 86%
“…24 Building evidence from highburden countries should be a priority and is essential to a complete understanding of health loss due to LRI. One qualitative study 25 revealed demandside barriers to healthcare utilisation in Nigeria, suggesting that costs, physical distance, cultural considerations, and knowledge of symptoms and warning signs might all play a role in delayed careseeking and could explain behaviours in other locations. In one study 26 of six countries in sub Saharan Africa, only 30% of care givers recognised fast breathing or difficulty in breathing as a symptom of LRI.…”
Section: Discussionmentioning
confidence: 99%
“…These include prolonged waiting times, poor communication between staff and patients, and negative previous experiences. 27 Despite an adequate number of health facilities, Homabay county suffers from inequities in health worker distribution. Even though there are an average of four doctors and 51 nurses per 100,000 populations, 58% of residents have to travel at least 5 km to the nearest health facility.…”
Section: Methodsmentioning
confidence: 99%